Improved single photon time resolution for analog SiPMs with front end readout that reduces influence of electronic noise. (19th September 2018) - Cates, Joshua W; Gundacker, Stefan; Auffray, Etiennette; Lecoq, Paul; Levin, Craig S
Abstract: A key step to improve the coincidence time resolution of positron emission tomography detectors that exploit small populations of promptly emitted photons is improving the single photon time resolution (SPTR) of silicon photomultipliers (SiPMs). The influence of electronic noise has previously been identified as the dominant factor affecting SPTR for large area, analog SiPMs. In this work, we measure the achievable SPTR with front end electronic readout that minimizes the influence of electronic noise. With this readout circuit, the SPTR measured for one FBK NUV single avalanche photodiode (SPAD) was also achieved with a mm 2 FBK NUV SiPM. SPTR for large area devices was also significantly improved. The measured SPTRs for mm 2 Hamamatsu and SensL SiPMs were 150 ps FWHM, and SPTR 100 ps FWHM was measured for mm 2 and mm 2 FBK NUV and NUV-HD SiPMs. We also explore additional factors affecting the achievable SPTR for large area, analog SiPMs when the contribution of electronic noise is minimized and pinpoint potential areas of improvement to further reduce the SPTR of large area sensors towards that achievable for a single SPAD.